The mutant of rs2075604 in STK11 improves HDL-c levels among newly diagnosed type 2 diabetes mellitus patients - Dita Maria Virginia; Christine Patramurti; Phebe Hendra; Paulina Nadya Feranti Pebby Lorenza; Faustina Evania Ngai; Novita Anastasia; Matea Nirmala Defi; Mae Sri Hartati Wahyuningsih; Dwi Aris Agung Nugrahaningsih (GarVal Editorial Ltda., 2023)
Context: Type 2 diabetes mellitus (T2DM) patients tend to have lipid abnormalities, thus elevating the risk of complications and mortality. Early detection using a genomic approach could help identify the abnormality of lipid profiles so that it could reduce those burdens. A previous study found a high frequency of mutants in the rs2075604 as the intron area in the STK11 gene. Aims: To analyze the effect of rs2075604 related to lipid abnormalities in newly diagnosed T2DM patients. Methods: This present study conducted a cross-sectional study in the ten public healthcare facilities in Sleman, Yogyakarta. The genetic variants were detected using PCR-RFLP methods. A total of 130 patients who had to consume antidiabetic oral for three months participated in this study. Results: This study revealed that the mutant variant dominated in this population at 61.5%. Mutant genotype, mutant allele, and dominant model reduce the risk of low HDL (OR = 0.33, 95% CI = 0.11-0.99; OR = 0.46, 95% CI = 0.24-0.90; OR = 0.33, 95% CI = 0.12-0.96; respectively). The improvement of low HDL risk by the mutant allele was confirmed through an adjusted model (OR = 0.47, 95% CI = 0.23-0.98). The mutant allele only influenced high LDL risk in the non-adjusted model (OR = 2.22, 95% CI = 1.02-4.82), but it did not found in other models. Conclusions: The mutant of rs2075604 has a protective role in low HDL-c risk in Indonesia. However, further study is required to observe the effect on LDL-c.